Unusual Presentation of an Ununited Anconeal Process in a Six-Year-Old Great Dane - Sikkema, Deborah A.; Roush, J. K. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
An acute weight-bearing, right forelimb lameness developed in a six-year-old Great Dane without any prior history of lameness. Clinical and radiographic findings were consistent with right ununited anconeal process and degenerative joint disease within the elbow, however, radiographically the anconeal process was separated from the ulna and attached to the humerus. Removal of the anconeal process resulted in satisfactory right front limb use for a further 40 months following the operation.
Keywords: Ununited anconeal process